Platinum nanoparticles from size adjusted functional colloidal particles generated by a seeded emulsion polymerization process - Vogel, Nicolas; et al. (Beilstein Journal of Nanotechnology, 2011)
The benefits of miniemulsion and emulsion polymerization are combined in a seeded emulsion polymerization process with functional seed particles synthesized by miniemulsion polymerization. A systematic study on the influence of different reaction parameters on the reaction pathway is conducted, including variations of the amount of monomer fed, the ratio of initiator to monomer and the choice of surfactant and composition of the continuous phase. Critical parameters affecting the control of the reaction are determined. If carefully controlled, the seeded emulsion polymerization with functional seed particles yields monodisperse particles with adjustable size and functionalities. Size-adjusted platinum-acetylacetonate containing latex particles with identical seed particles and varied shell thicknesses are used to produce arrays of highly ordered platinum nanoparticles with different interparticle distances but identical particle sizes. For that, a self-assembled monolayer of functional colloids is prepared on a solid substrate and subsequently treated by oxygen plasma processing in order to remove the organic constituents. This step, however, leads to a saturated state of a residual mix of materials. In order to determine parameters influencing this saturation state, the type of surfactant, the amount of precursor loading and the size of the colloids are varied. By short annealing at high temperatures platinum nanoparticles are generated from the saturated state particles. Typically, the present fabrication method delivers a maximum interparticle distance of about 260 nm for well-defined crystalline platinum nanoparticles limited by deformation processes due to softening of the organic material during the plasma applications.
Keywords: colloid lithography; functional colloids; miniemulsion polymerization; nanoparticles; seeded emulsion polymerization